The Economics of Wagering Markets - Sauer, Raymond D. (Journal of Economic Literature, 1998)
Wagering markets provide a natural laboratory for testing models of market prices and behavior under uncertainty. The literature on wagering, albeit contentious, has established the following. First, prices set in these markets, to a first approximation, are efficient forecasts of outcomes. Second, price changes in these markets are driven by an informed class of bettors and improve prediction. Nevertheless, there are important departures from generic notions of market efficiency. Recent models focusing on diverse information, heterogeneous agents, and transaction costs help to explain these findings.